2009
DOI: 10.3171/2009.3.focus0962
|View full text |Cite
|
Sign up to set email alerts
|

Complications of cranioplasty following decompressive craniectomy: analysis of 62 cases

Abstract: Object Decompressive craniectomy is a potentially life-saving procedure used in the treatment of medically refractory intracranial hypertension, most commonly in the setting of trauma or cerebral infarction. Once performed, surviving patients are obligated to undergo a second procedure for cranial reconstruction. The complications following cranial reconstruction are not well described in the literature and may very well be underreported. A review of the complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
269
4
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 391 publications
(298 citation statements)
references
References 67 publications
17
269
4
8
Order By: Relevance
“…1). We defined EFC as low density fluid in the epidural space on brain CT scan Data from recent studies have indicated that cranioplasty following decompressive craniectomy was associated with a high complication rates, ranged from 16.4% to 34% 4,6,8,12) . However, these studies mainly analyzed on major complications including infection, hematoma formation, and bone flap resorption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). We defined EFC as low density fluid in the epidural space on brain CT scan Data from recent studies have indicated that cranioplasty following decompressive craniectomy was associated with a high complication rates, ranged from 16.4% to 34% 4,6,8,12) . However, these studies mainly analyzed on major complications including infection, hematoma formation, and bone flap resorption.…”
Section: Discussionmentioning
confidence: 99%
“…The complications, including infection, hematoma, and bone graft resorption following cranioplasty have been well studied and considered as a significant cause of postoperative morbidity 6,8,11,12) . However, reports of epidural fluid collection (EFC) after cranioplasty are uncommon and limited to isolated case examples and small series 6,10) .…”
Section: Introductionmentioning
confidence: 99%
“…The first studies using fiber-reinforced composites (FRCs) in medicine and dentistry occurred in the early 1960s, but more extensive research started in the early 1990s which led to introduction of FRCs as reconstructive material for damaged dental hard tissues [14][15][16][17][18]. The first approved surgical applications were found in cranial surgery [18].…”
Section: Introductionmentioning
confidence: 99%
“…3 This may be so for a number of reasons, not least of which is the morbidity associated with not only the initial decompressive surgery but also the subsequent cranioplasty. 5,7,21 One issue that has received relatively little attention relates to the management of the temporal muscle, which is problematic for a number of reasons (Fig. 1). 1 First, the muscle often becomes damaged when it is detached from the temporal bone during the initial craniectomy procedure.…”
mentioning
confidence: 99%
“…Dissecting the muscle can increase the risk of postoperative hematoma formation, which is a relatively common complication following cranioplasty. 2,5,18 Finally, there are functional and aesthetic problems that relate to muscle loss leading to masticatory difficulties and an unsatisfactory appearance due to temporal hollowing (Fig. 3).…”
mentioning
confidence: 99%